Child soldier reality in Uganda: International law and reintegration - Dalaman, Zeynep Banu; Parlak, Türkan Melis (Border Crossing, 2020)
The use of children who have been most exposed to the destructive effects of wars for various military activities has been seen throughout history. Child soldiers are involved in civil wars and conflicts in many countries, especially in Africa, without discrimination. Even if the participation of 15-year-olds in the Army is accepted as a war crime by the United Nations, some 300,000 children are actively involved in wars today. The key to child soldiers is the reintroduction and retraining of these children. However, what should be mentioned here is that these children are guilty? Or a victim? In this article, the child soldier problem will be discussed from two angles. First, the effectiveness of the decisions taken to prevent criminal organisations and states from committing this crime to recruit child soldiers within the framework of international law rules will be discussed. Secondly, based on the example of Uganda, the programs prepared by the international community for the reintegration of former child warriors to society will be analysed.